The effect of rootstock on the growth and yielding of ‘Regina’ cherry trees - Wociór Stanisław (Folia Horticulturae, 2008)
The studies conducted in the years 2004 - 2006 in a production orchard in the habitat conditions of the Wyżyna Sandomierska showed that the trees budded on Mazzard seedling grew more strongly than on Colt rootstock. No significant differences were observed between the rootstocks as for the trunk thickness and the crown size of young trees planted in 2001. In the group of trees planted in 1996, which were in the period of full fruiting, the crowns of trees budded on Mazzard seedling were significantly bigger than on Colt rootstock. No significant differences were found in the yielding of trees grafted on Mazzard seedling and Colt rootstock. Considerable differences in the yielding between the studied years in the group of older trees point to a big influence of the weather on the fruiting of cherry. A significant decrease of the yield in 2005 was caused by spring ground frost, while in 2006 by frozen short shoots in winter. ‘Regina’ is a valuable cultivar for production planting in the Wyżyna Sandomierska. It begins the fruiting period late (the first commercial yield in the fifth year after planting); however, it gives attractive fruits, resistant to cracking in the rain. ‘Regina’ yielded abundantly on both examined rootstocks.